Evaluation method for improvement effect of solid-state battery composite pole piece on internal short circuit and application
By simulating the internal short circuit mode and measuring the short circuit resistance of the solid-state battery composite electrode sheet, the problem of lack of quantitative evaluation of the short circuit safety of solid-state composite electrodes to the battery in the prior art is solved, and a quantitative evaluation of the improvement of battery safety is achieved.
Patent Information
- Application Number
- CN202411533948.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-11
AI Technical Summary
The prior art lacks effective quantitative evaluation methods to characterize the improvement of the short circuit safety of solid-state composite electrodes in the battery, especially at the pole-sheet level.
By simulating different internal short circuit modes, the surface contact resistance between solid-state battery composite pole plates and between pole plates and current collectors is measured, and the effect of improving its internal short circuit impedance is quantified. The method includes preparing a test sample, applying a predetermined pressure, and measuring the short circuit resistance using a resistance measurement system.
It provides the ability to quantitatively evaluate the improved battery safety effect of solid-state composite electrodes, can accurately measure changes in short-circuit resistance, and helps to design and manufacture solid-state batteries scientific basis and guidance.
Smart Images

Figure CN119414276A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of evaluating short-circuit resistance between battery electrodes, and specifically relates to an evaluation method and application of the improvement effect of a composite pole piece of a solid-state battery on internal short circuit. Background Art
[0002] As the demand for electric vehicles and portable electronic devices continues to increase, lithium / sodium-ion batteries have become a widely used battery technology due to their higher energy density and longer cycle life compared to traditional batteries. At present, the safety of lithium / sodium-ion batteries remains one of the focuses of general concern in the industry.
[0003] In normal conditions, the positive and negative electrodes of lithium / sodium-ion batteries are separated by a porous diaphragm to prevent the two electrodes from directly contacting and causing a short circuit. However, when an abnormality occurs and causes the diaphragm to shrink or break, the probability of an internal short circuit in the battery increases greatly. At this time, discharge at the short-circuit point generates heat, and the heat continues to accumulate, leading to thermal runaway. There are four possible situations for internal micro-short circuits: ① Short circuit between the positive electrode collector and the negative electrode material, ② Short circuit between the negative electrode collector and the positive electrode material, ③ Short circuit between the positive and negative electrode collectors, and ④ Short circuit between the positive and negative electrode materials.
[0004] In order to improve the intrinsic safety of traditional liquid batteries, solid-state / semi-solid-state battery technology was born. In new solid-state or semi-solid-state batteries, a solid composite electrode is formed by coating a solid electrolyte layer on the surface of the electrode (positive electrode, negative electrode). Since solid electrolyte materials have the characteristics of ion conductivity and electronic insulation, even if a micro short circuit occurs internally, the short-circuit resistance during the internal short circuit can be greatly improved, and the short-circuit current can be effectively suppressed, thereby limiting the internal short circuit heating, thereby avoiding the accumulation of heat at the internal short circuit point and the stimulation of thermal runaway.
[0005] The evaluation method for improving the internal short-circuit safety of solid-state composite electrodes is currently more focused on the battery cell level, and the safety of the battery cell is evaluated through safety abuse simulation tests such as needle puncture, extrusion, and hot box. However, battery cell safety is a systematic project, which is closely related to factors such as battery cell design, process technology, foreign matter control, and material stability. At the electrode level, the industry still lacks an effective evaluation method to quantitatively characterize the improvement effect of solid-state composite electrodes on safety. Summary of the invention
[0006] In view of the shortcomings of the prior art, the present invention provides an evaluation method for solid-state battery composite electrode sheets. By simulating corresponding internal short-circuit failure scenarios, the short-circuit electronic resistance characteristics under different internal short-circuit modes are evaluated. By measuring the surface contact resistance between electrode sheets and between electrode sheets and current collectors, the specific effect of solid-state electrodes on improving the internal short-circuit impedance is quantified, thereby providing effective reference and design guidance for the safety design and evaluation of solid-state battery cells.
[0007] The first aspect of the present invention is to provide a method for evaluating the improvement effect of a solid-state battery composite pole piece on an internal short circuit, comprising the following steps:
[0008] (a) preparing at least two test samples, at least one of which is a combination of a solid composite electrode sheet and a simulated short-circuit paired electrode sheet, and at least one of which is a combination of a non-solid composite electrode sheet and a simulated short-circuit paired electrode sheet;
[0009] (b) placing the test samples between a pair of metal pressing heads and applying a predetermined pressure;
[0010] (c) using a resistance measurement system to measure the short-circuit resistance of the test sample under the predetermined pressure;
[0011] (d) recording the short-circuit resistance value, and evaluating the impedance enhancement effect of the solid composite electrode sheet relative to the non-solid composite electrode sheet during short circuit according to the difference in the recorded short-circuit resistance values.
[0012] As a further optimization solution, the solid composite electrode sheet includes a current collector and an active material layer and a solid electrolyte layer arranged on at least one side of the current collector.
[0013] As a further optimization scheme, the active material layer is selected from positive electrode active materials or negative electrode active materials; wherein the positive electrode active material is selected from lithium iron phosphate, lithium manganese iron phosphate, lithium manganese oxide, lithium cobalt oxide, ternary material, lithium manganese-rich based material, layered sodium ion positive electrode material, Prussian white type sodium ion positive electrode material, polyanion type sodium ion positive electrode material; wherein the negative electrode active material is selected from graphite material, silicon-based material, hard carbon material, lithium titanate material, niobium titanium oxide material.
[0014] As a further optimization scheme, the solid electrolyte layer uses a non-polar solid electrolyte material selected from LATP, LAGP, LLZO, LLZTO, LGPS, LPSCl, Li3YCl6, and Li3YBr6.
[0015] As a further optimization solution, the thickness of the solid electrolyte layer ranges from 1 to 50 um.
[0016] As a further optimization solution, the current collector is an aluminum current collector with a thickness of 4 to 30 um or a copper current collector with a thickness of 3 to 20 um.
[0017] As a further optimization solution, the surface roughness of the metal pressure head is Ra≤5um.
[0018] As a further optimization solution, the metal indenter applies a predetermined pressure of 200 kPa to 200 MPa to the test sample and maintains the predetermined pressure for more than 20 seconds.
[0019] As a further optimization solution, the resistance measurement system includes a voltage measurement system and a current measurement system, and the resistance value is determined by calculating the voltage / current ratio.
[0020] The second aspect of the present invention is to provide an application of the above-mentioned method for evaluating the improvement effect of the solid-state battery composite electrode on internal short circuit, which is used in optimizing the design of solid-state battery safety and / or in quantitatively characterizing the improvement effect of the solid-state composite electrode on safety at the electrode level.
[0021] Beneficial Effects
[0022] The method of the present invention provides the ability to quantitatively evaluate the effect of solid composite electrodes on improving battery safety. By testing samples of different combinations, the change in short-circuit resistance can be accurately measured, thereby providing reliable data support for the design of solid-state batteries.
[0023] The method of the present invention can be used to more accurately simulate the internal short circuit of the battery and verify the short circuit resistance of the solid composite electrode compared with the traditional liquid battery electrode when short-circuited.
[0024] The method of the present invention is suitable for simulating and testing different short-circuit modes, including contact between the positive electrode collector and the negative electrode material, contact between the negative electrode collector and the positive electrode material, and direct contact between the positive and negative electrode materials, and can comprehensively evaluate the performance of the solid-state composite electrode under various possible short-circuit situations.
[0025] By comparing the changes in short-circuit resistance under different conditions through the method of the present invention, engineers can understand and analyze the contribution of different design elements to improving battery safety, thereby providing a scientific basis and guidance for the design and manufacture of solid-state batteries.
[0026] The present invention also provides a standardized testing method, so that comparable results can be obtained between different laboratories or manufacturers, which helps to promote the establishment and development of industry standards. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 Schematic diagram of the test method for evaluating solid-state battery composite electrode sheets.
[0028] Figure 2 Test flow chart for the evaluation method of solid-state battery composite electrode sheets.
[0029] Figure 3 Schematic diagram of the structure of the current collector test sample.
[0030] Figure 4 Schematic diagram of the structure of the single-sided coated pole piece test sample.
[0031] Figure 5Schematic diagram of the structure of a single-sided coated solid composite pole piece test sample.
[0032] Figure 6 Schematic diagram of the structure of the double-sided coated pole piece test sample.
[0033] Figure 7 Schematic diagram of the structure of the double-sided coated solid composite electrode test sample. DETAILED DESCRIPTION
[0034] The present invention is further illustrated by specific examples below. These examples are exemplary and are intended to illustrate the problem and explain the present invention, but are not intended to be limiting.
[0035] The test mechanism used in the evaluation method of the present invention is as follows Figure 1 As shown, it includes a metal upper press head 11 and a metal lower press head 12 facing each other, the gap between the metal upper press head 11 and the metal lower press head 12 is used to place the test sample 5, a voltage measurement system 2 and a current measurement system 3 are connected between the metal upper press head 11 and the metal lower press head 12, and an external pressure mechanism 4 is provided above the metal upper press head 11 to provide extrusion force.
[0036] The voltage measurement system 2 and the current measurement system 3 together constitute a resistance measurement system, and the resistance measurement range is between 0.01mΩ and 10kΩ. The test sample 5, the metal upper pressure head 11, the metal lower pressure head 12, and the resistance measurement system together form a current loop. The system can record voltage and current at the same time. The resistance value is determined by the voltage / current ratio, that is, Ohm's law.
[0037] Among them, the cross-sectional shapes of the metal upper pressure head 11 and the metal lower pressure head 12 can be selected in a variety of ways, such as circular, square, hexagonal, triangular, etc., and a circular cross-sectional shape is typically used. The cross-sectional areas of the metal upper pressure head 11 and the metal lower pressure head 12 are not without special restrictions. Taking a circular shape as an example, a typical diameter is 5 to 30 mm. The material of the metal upper pressure head 11 and the metal lower pressure head 12 is a conductive metal material, and a stainless steel material is typically selected.
[0038] The surfaces of the metal upper pressing head 11 and the metal lower pressing head 12 are kept parallel, and the surface roughness of the metal upper pressing head 11 and the metal lower pressing head 12 is Ra≤5um, typically Ra≤0.5um.
[0039] Test process such as Figure 2As shown, in order to evaluate the electronic short-circuit resistance characteristics of the solid-state battery composite electrode sheet under different internal short-circuit modes, the electrode sheet or current collector sample to be tested is cut into a predetermined size, the shape after cutting is consistent, and the area after cutting is guaranteed to completely cover the upper and lower probes; according to the test requirements, it can be combined to obtain a test sample 5; then the combined sample is placed between the metal upper pressure head 11 and the metal lower pressure head 12 on the test bench, and an external pressure mechanism 4 is used to apply a certain extrusion force to the metal upper pressure head 11 to simulate the contact conditions in actual use; start the resistance measurement system connected to the metal pressure head, which includes a voltage measurement system 2 and a current measurement system 3. It is used to measure the voltage and current data of the sample under pressure. Through the collected data, the ohmic resistance can be calculated or the resistance value can be directly read from the system. By comparing and analyzing the short-circuit resistance changes between different sample combinations, the effect of the solid-state composite electrode on the improvement of the internal short-circuit impedance can be quantified, thereby providing a scientific basis for the safety design of solid-state batteries.
[0040] Current collector 91 Figure 3 As shown, the current collector 91 is an aluminum current collector, a copper current collector, etc. Among them, the thickness of the aluminum foil is 4 to 30 um, preferably 10 to 16 um; the thickness of the copper foil is 3 to 20 um, preferably 4 to 8 um.
[0041] The single-sided coated electrode sheet can be a single-sided coated positive electrode sheet or a single-sided coated negative electrode sheet, such as Figure 4 As shown, the single-sided coated electrode sheet includes a current collector 91 and an active material layer 92 on one side.
[0042] The single-sided coated solid composite electrode sheet can be a single-sided coated solid composite positive electrode sheet or a single-sided coated solid composite negative electrode sheet, such as Figure 5 As shown, the single-sided coated solid composite electrode comprises a current collector 91 and an active material layer 92 and a surface dielectric layer 93 located on one side.
[0043] The double-sided coated electrode can be a double-sided coated positive electrode or a double-sided coated negative electrode, such as Figure 6 As shown, the double-sided coated electrode includes a current collector 91 and active material layers 92 on both sides.
[0044] The double-sided coated solid composite electrode sheet can be a double-sided coated solid composite positive electrode sheet or a double-sided coated solid composite negative electrode sheet, such as Figure 7 As shown, the double-sided coated solid composite electrode comprises a current collector 91 and active material layers 92 and a surface dielectric layer 93 located on both sides.
[0045] Test sample 5 can be selected from a combination of the above two, including: aluminum current collector / single-sided coated negative electrode sheet, copper current collector / single-sided coated positive electrode sheet, aluminum current collector / double-sided coated negative electrode sheet, copper current collector / double-sided coated positive electrode sheet, aluminum current collector / single-sided coated composite solid negative electrode sheet, copper current collector / single-sided coated composite solid positive electrode sheet, single-sided coated negative electrode sheet / single-sided coated positive electrode sheet, single-sided coated composite solid negative electrode sheet / single-sided coated composite solid positive electrode sheet, double-sided coated composite solid negative electrode sheet / double-sided coated composite solid positive electrode sheet, etc.
[0046] The active materials of the electrode sheet may include positive electrode active materials and negative electrode active materials, wherein the positive electrode active materials include lithium iron phosphate, lithium iron manganese phosphate, lithium manganese oxide, lithium cobalt oxide, ternary materials, lithium-rich manganese-based materials, layered sodium ion positive electrode materials, Prussian white sodium ion positive electrode materials, polyanion sodium ion positive electrode materials, etc.; the negative electrode active materials include graphite materials, silicon-based materials (silicon dioxide materials, silicon-carbon composite materials, etc.), hard carbon materials, lithium titanate materials, niobium titanium oxide materials, etc.
[0047] The composite electrode surface electrolyte layer is selected from non-polar solid electrolyte materials such as oxides, sulfides, halides, etc., such as LATP, LAGP, LLZO, LLZTO, LGPS, LPSCl, Li3YCl6, Li3YBr6. The thickness of the composite electrode surface electrolyte layer ranges from 0 to 50um, such as 2 to 4um, 4 to 8um, 8 to 12um, etc.
[0048] The electrode sheets may be either unrolled or rolled. The rolling compaction degree of the negative electrode sheet (including the composite negative electrode sheet) is designed to be between 0.6 and 1.8, typically between 1.0 and 1.65; the rolling compaction degree of the positive electrode sheet (including the composite positive electrode sheet) is designed to be between 2.0 and 4.2, typically between 2.2 and 3.8.
[0049] The sample is punched into a suitable size before testing, which is required to completely cover the test probe. Typically, if the probe diameter is 10mm, the sample diameter can be punched into 12mm~18mm;
[0050] The applied pressure F is continuously adjustable. The pressure system is equipped with a pressure sensor to adjust the pressure at the probe position in real time. The pressure F / A meets the range of 0 to 200 MPa, such as 350 kPa, 1 MPa, and 25 MPa, and can be set according to specific needs.
[0051] A typical test method includes the following steps:
[0052] S1: prepare a single-layer coated composite solid positive electrode sheet and cut the electrode sheet into required specifications;
[0053] S2: preparing a single-layer coated negative electrode sheet and cutting the negative electrode sheet into required specifications;
[0054] S3: Cover the negative electrode sample on the surface of the composite positive electrode sample, wherein the negative electrode active material layer and the positive electrode material layer are bonded to each other, ensuring that they are consistent with the combination of the internal resistance electrode of the battery cell;
[0055] S4: Place the above-mentioned object combination to be tested on the sample table of the test equipment (i.e., the surface of the metal lower pressure head 12), set the pressure parameters, and start the equipment so that the upper pressure head presses against the test sample;
[0056] S5: until the target pressure is reached and maintained stable for more than 20 seconds;
[0057] S6: Start the resistance measurement system, test the ohmic impedance, and record the resistance value;
[0058] S7: Replace other object combinations, repeat the above measurement process, and record the resistance data.
[0059] The above method is used to simulate various possible positive and negative short-circuit contact situations when there is a micro-short circuit inside the battery cell, measure the short-circuit impedance under the corresponding conditions, and compare the improvement effect of the solid-state composite electrode on the short-circuit impedance.
[0060] Example 1 (6um copper foil / single-sided NCM composite positive electrode)
[0061] Prepare a single-sided coated composite positive electrode sheet. The active material is a ternary NCM material, the surface electrolyte material is a LATP solid electrolyte material, and the compaction degree of the composite electrode sheet is 3.5g / cm 3 The single-sided surface density of the active material layer is 180g / m 2 , the surface electrolyte layer thickness is 4±1um; prepare the negative electrode current collector copper foil with a thickness of 6um. Punch the above-mentioned pole piece and copper foil into discs with a diameter of 14mm, 10 pieces each. Cover the copper foil on the electrode material / surface coating side of the composite pole piece as a test object combination to simulate the scenario where the negative electrode current collector is connected to the positive electrode during a micro-short circuit. Place the test object on the test probe, set the pressure to 1MPa, and connect the resistance test system. Start the pressure system, read the resistance data 20 seconds after reaching the target pressure value; take out the sample after depressurization. Repeat 10 times in sequence to complete the test of 10 groups of sample combinations, take the average value, deduct the system's own ohmic impedance R0 (comparison example 0), and record the impedance as R1.
[0062] Example 2 (12um aluminum foil / single-sided graphite coated composite negative electrode)
[0063] Prepare a single-sided coated composite negative electrode sheet. The active material is graphite material, the surface electrolyte material is LATP solid electrolyte material, and the compaction degree of the composite electrode sheet is 1.55g / cm 3 The single-sided surface density of the active material layer is 118 g / m2 , the surface electrolyte layer thickness is 4±1um; prepare the positive electrode collector aluminum foil with a thickness of 12um. Punch the above-mentioned pole piece and copper foil into discs with a diameter of 14mm, 10 pieces each. Cover the copper foil on the electrode material / surface coating side of the composite pole piece as a test object combination to simulate the scenario where the positive electrode collector is connected to the negative electrode during a micro-short circuit. Place the test object on the test probe, set the pressure to 1MPa, and connect the resistance test system. Start the pressure system, read the resistance data 20 seconds after reaching the target pressure value; take out the sample after depressurization. Repeat 10 times in sequence to complete the test of 10 groups of sample combinations, take the average value, deduct the system's own ohmic impedance R0 (comparison example 0), and record the impedance as R2.
[0064] Example 3 (single-sided coating of NCM composite positive electrode / single-sided coating of graphite composite negative electrode)
[0065] Prepare a single-sided coated composite positive electrode sheet. The active material is a ternary NCM material, the surface electrolyte material is a LATP solid electrolyte material, and the compaction degree of the composite electrode sheet is 3.5g / cm 3 The single-sided surface density of the active material layer is 180g / m 2 , the surface electrolyte layer thickness is 4±1um; prepare a single-sided coated composite negative electrode sheet, the active material is graphite material, the surface electrolyte material is LATP solid electrolyte material, and the compaction degree of the composite electrode sheet is 1.55g / cm 3 The single-sided surface density of the active material layer is 118 g / m 2 , the thickness of the surface electrolyte layer is 4±1um; the above-mentioned positive and negative composite electrodes are punched into discs with a diameter of 14mm, 10 pieces each. The positive and negative composite electrodes are bonded to each other, and the electrode material layers are in contact with each other, as a test object combination, to simulate the scenario where the positive and negative electrode material areas overlap each other during a micro-short circuit. Place the test object on the test probe, set the pressure to 1MPa, and connect the resistance test system. Start the pressure system, read the resistance data 20 seconds after reaching the target pressure value; take out the sample after depressurization. Repeat the test of 10 groups of sample combinations 10 times in sequence, take the average value, deduct the system's own ohmic impedance R0 (comparison example 0), and record the impedance as R3.
[0066] Comparative Example 0 (System Ohmic Impedance)
[0067] To calibrate the internal resistance of the test system itself, there is no need to prepare samples. Set the pressure to 1MPa, connect the resistance test system, start the pressure system, and make the upper and lower probes directly contact each other. After 20 seconds of reaching the target pressure value, read the resistance data; repeat the measurement 10 times and take the average value R0, which is the ohmic impedance of the test system itself.
[0068] Comparative Example 1 (6um copper foil / single-sided NCM positive electrode coating)
[0069] Prepare a single-sided coated positive electrode sheet. The active material is a ternary NCM material. The compaction of the electrode sheet is 3.5g / cm 3 The single-sided surface density of the active material layer is 180g / m 2 ; Prepare the negative electrode current collector copper foil with a thickness of 6um. Punch the above-mentioned pole piece and copper foil into discs with a diameter of 14mm, 10 pieces each. Cover the copper foil on the electrode material side as a test object combination to simulate the scenario where the negative electrode current collector is connected to the positive electrode during a micro-short circuit. Place the test object on the test probe, set the pressure to 1MPa, and connect the resistance test system. Start the pressure system, read the resistance data 20 seconds after reaching the target pressure value; take out the sample after depressurization. Repeat the test of 10 groups of sample combinations 10 times in sequence, take the average value, deduct the system's own ohmic impedance R0 (comparison example 0), and record the impedance as r1.
[0070] Comparative Example 2 (12um aluminum foil / single-sided graphite negative electrode)
[0071] Prepare a single-sided coated negative electrode sheet. The active material is graphite material and the compaction of the electrode sheet is 1.55g / cm 3 The single-sided surface density of the active material layer is 118 g / m 2 ; Prepare aluminum foil for the positive electrode current collector with a thickness of 12um. Punch the above-mentioned pole piece and aluminum foil into discs with a diameter of 14mm, 10 pieces each. Cover the aluminum foil on the electrode material side of the negative electrode sheet as a test object combination to simulate the scenario where the positive electrode current collector is connected to the negative electrode during a micro-short circuit. Place the test object on the test probe, set the pressure to 1MPa, and connect the resistance test system. Start the pressure system, and read the resistance data 20 seconds after reaching the target pressure value; take out the sample after depressurization. Repeat the test of 10 groups of sample combinations 10 times in sequence, take the average value, deduct the system's own ohmic impedance R0 (comparison example 0), and record the impedance as r2.
[0072] Comparative Example 3 (single-sided NCM positive electrode / single-sided graphite negative electrode)
[0073] Prepare a single-sided coated positive electrode sheet. The active material is a ternary NCM material. The compaction of the electrode sheet is 3.5g / cm 3 The single-sided surface density of the active material layer is 180g / m 2 ; Prepare a single-sided coated negative electrode sheet, the active material is graphite material, and the compaction of the electrode sheet is 1.55g / cm 3 The single-sided surface density of the active material layer is 118 g / m 2; Punch the above-mentioned positive and negative electrodes into discs with a diameter of 14 mm, 10 pieces each. Fit the positive and negative composite electrodes to each other, and the electrode material layers are in contact with each other, as a test object combination, to simulate the scenario where the positive and negative electrode material areas overlap each other during a micro-short circuit. Place the test object on the test probe, set the pressure to 1MPa, and connect the resistance test system. Start the pressure system, and read the resistance data 20 seconds after reaching the target pressure value; take out the sample after depressurizing. Repeat the test 10 times in sequence to complete 10 groups of sample combinations, take the average value, and then deduct the system's own ohmic impedance R0 (comparison example 0), and record the impedance as r3.
[0074] The impedances measured in the above embodiments and comparative examples are shown in Table 1.
[0075]
[0076] Through the test results of Example 1 and Comparative Example 1, it can be seen that when a short circuit occurs in the negative electrode current collector and the positive electrode material area (the contact area of the short circuit point is a circular area with a diameter of 10 mm), based on the evaluation method described in the present invention, the short-circuit resistance of the solid composite electrode after the short circuit with the copper foil is significantly higher than the short-circuit resistance of the conventional positive electrode and the copper foil, increasing from 11.3Ω to 496Ω, an increase of more than 40 times. This is because the ceramic electrolyte on the surface of the composite positive electrode has electronic insulation properties. Even if a short circuit occurs, electrons are conducted from the positive electrode active material area to the negative electrode current collector, and need to tunnel through the ceramic insulation layer on the positive electrode surface, so the short-circuit resistance is greatly improved. It can be seen from the test results that the method described in the present invention can compare the short-circuit internal resistance of pole pieces of different designs when a short circuit occurs, and can quantitatively evaluate the improvement effect of the short-circuit impedance of the composite pole piece under the condition of an internal short circuit.
[0077] Through the test results of Example 2 and Comparative Example 2, it can be seen that when a short circuit occurs in the positive current collector and the negative electrode material area (the contact area of the short circuit point is a circular area with a diameter of 10 mm), due to the good electronic conductivity of the graphite material itself, the overall short-circuit internal resistance is reduced relative to the positive electrode. Even so, the short-circuit resistance after the solid composite electrode and the aluminum foil are short-circuited is significantly higher than the short-circuit resistance of the conventional positive and negative electrodes and the aluminum foil short-circuited, increasing from 0.39Ω to 3.2Ω, an increase of about 8 times. This is also due to the fact that the ceramic electrolyte on the surface of the composite negative electrode has electronic insulation properties. Even if a short circuit occurs, electrons are conducted from the positive active material area to the positive current collector, and it is necessary to tunnel through the ceramic insulating layer on the surface, so the short-circuit resistance is increased. It can be seen from the test results that the method described in the present invention can also be used to quantitatively evaluate the short circuit in the composite negative electrode-positive current collector.
[0078] Through the test results of Example 3 and Comparative Example 3, it can be seen that when the positive and negative electrode material areas are in contact with each other and short-circuited (the short-circuit point contact area is the prototype area with a diameter of 10 mm), based on the evaluation method described in the present invention, the short-circuit resistance between the solid composite electrodes is much higher than the conventional positive and negative electrode short-circuit resistance, increasing from 23.6Ω to more than 3000Ω. This is due to the dual effect of the ceramic electrolyte on the surface of the composite positive and negative electrodes, which makes it extremely difficult for electrons to conduct, so the short-circuit resistance is greatly improved, which is theoretically better for improving the safety of short circuits in the battery cell. It can be seen from the test results that the method described in the present invention can quantitatively evaluate the short-circuit resistance characteristics between the composite positive and negative electrodes.
[0079] The above embodiments are exemplary, and their purpose is to illustrate the technical concept and features of the present invention so that people familiar with the technology in this field can understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for evaluating the improvement effect of a solid-state battery composite electrode on internal short circuit, characterized in that: The following steps are involved: (a) preparing at least two test samples, at least one of which is a combination of a solid composite electrode sheet and a simulated short-circuit paired electrode sheet, and at least one of which is a combination of a non-solid composite electrode sheet and a simulated short-circuit paired electrode sheet; (b) placing the test samples between a pair of metal indenters and applying a predetermined pressure; (c) measuring the short-circuit resistance of the test sample under the predetermined pressure using a resistance measurement system; (d) recording the short-circuit resistance value, and evaluating the impedance enhancement effect of the solid composite electrode sheet relative to the non-solid composite electrode sheet during short circuit according to the difference in the recorded short-circuit resistance values.
2. The method for evaluating the improvement effect of a solid-state battery composite electrode on internal short circuit according to claim 1, characterized in that: The solid composite electrode sheet includes a current collector and an active material layer and a solid electrolyte layer disposed on at least one side of the current collector.
3. The method for evaluating the improvement effect of the solid-state battery composite pole piece on the internal short circuit according to claim 2, characterized in that: The active material layer is selected from positive electrode active materials or negative electrode active materials; wherein the positive electrode active material is selected from lithium iron phosphate, lithium manganese iron phosphate, lithium manganese oxide, lithium cobalt oxide, ternary materials, lithium-rich manganese-based materials, layered sodium ion positive electrode materials, Prussian white sodium ion positive electrode materials, polyanion sodium ion positive electrode materials; wherein the negative electrode active material is selected from graphite materials, silicon-based materials, hard carbon materials, lithium titanate materials, and niobium titanium oxide materials.
4. The method for evaluating the improvement effect of a solid-state battery composite electrode on internal short circuit according to claim 2, characterized in that: The solid electrolyte layer is made of non-polar solid electrolyte material, selected from LATP, LAGP, LLZO, LLZTO, LGPS, LPSCl, Li3YCl6, and Li3YBr6.
5. The method for evaluating the improvement effect of a solid-state battery composite electrode on internal short circuit according to claim 4, characterized in that: The thickness of the solid electrolyte layer ranges from 1 to 50 um.
6. The method for evaluating the improvement effect of a solid-state battery composite electrode on internal short circuit according to claim 2, characterized in that: The current collector is an aluminum current collector with a thickness of 4 to 30 um or a copper current collector with a thickness of 3 to 20 um.
7. The method for evaluating the improvement effect of a solid-state battery composite electrode on internal short circuit according to claim 1, characterized in that: The surface roughness of the metal pressure head is Ra≤5um.
8. The method for evaluating the improvement effect of a solid-state battery composite electrode on internal short circuit according to claim 1, characterized in that: The metal indenter applies a predetermined pressure of 200 kPa~200 MPa to the test sample and maintains the predetermined pressure for more than 20 seconds.
9. The method for evaluating the improvement effect of a solid-state battery composite electrode on internal short circuit according to claim 1, characterized in that: The resistance measurement system includes a voltage measurement system and a current measurement system, and the resistance value is determined by calculating the voltage / current ratio.
10. Application of the evaluation method according to any one of claims 1 to 9, characterized in that: The evaluation method is applied to quantitatively characterize the improvement effect of solid-state composite electrodes on safety in optimizing the safety design of solid-state batteries.
Citation Information
Cited By
Method for pre-judging mechanical safety of battery based on pole piece parameters
CN121703664A